Sinais e sintomas associados com a erupção de dentes decíduos: estudo longitudinal - Joana Ramos Jorge (2010)
The association between eruption of primary teeth and manifestation of signs and symptoms in infants is a controversial issue in literature. There is still no scientific evidence that supports this association. However, parents and health professionals continue to believe that eruption of primary teeth is because of the manifestion of signs and symptoms in infants. Thus, the aim of this study was Assess the association between primary tooth eruption and the manifestation of signs and symptoms in infants. A longitudinal study was carried out with 47 non-institutionalized infants between five and 15 months of age in the city of Diamantina, Brazil. The non-randomized convenience sample was based on a registry of infants provided by the Municipal Secretary of Health. Eligible participants were infants with between zero and seven erupted teeth and no history of chronic disease or disorders that could cause an increase in the symptoms assessed in the study. Tympanic and axillary temperature readings and clinical oral exams were performed daily. A daily interview with the mothers was carried to investigate the occurrence of 14 signs and symptoms associated to teething presented by the infants in the previous 24 hours. Teething was associated to a rise in tympanic temperature on the day of the eruption (P=0.004) as well as the occurrence of other signs and symptoms. Maximal tympanic and axillary temperature was 36.8 ºC and 36.6 ºC, respectively. The most frequent sign and symptoms associated to teething were irritability (P<0.001), increased salivation (P<0.001), runny nose (P<0.001) and loss of appetite (P<0.001). Signs and symptoms, such as irritability, increased salivation, runny nose, loss of appetite, diarrhea, rash and sleep disturbance, were associated to primary 12 tooth eruption. The present study supports the concept that the occurrence of severe signs and symptoms, such as fever, is not attributed to teething.